PENDIDIKAN KARAKTER DITINJAU DARI PERSPEKTIF PENDIDIKAN ISLAM (RELEVANSI PEMIKIRAN KI HAJAR DEWANTARA DAN IBNU MISKAWAIH) - Puspita Sari, Kharisma; Kadarismanto, Kadarismanto; Hakim, Ibnu (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
Character education has been discussed for a long time, but has not brought significant changes to the world of education, on the contrary. All elements are expected to work together in solving this problem. Among parents, teachers and the community can provide examples and teachings related to character education by looking at Ki Hajar Dewantara and Ibn Miskawaih. This study uses a qualitative method with a library research approach that leads to character thinking through sources such as documentation, books, and journals. With the results of the research, the two figures have the same concept related to character education, namely prioritizing moral or moral aspects in education.